2016
DOI: 10.1016/j.antiviral.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activities of niclosamide and nitazoxanide against chikungunya virus entry and transmission

Abstract: Chikungunya disease results from an infection with the arbovirus, chikungunya virus (CHIKV). Symptoms of CHIKV include fever and persistent, severe arthritis. In recent years, several antiviral drugs have been evaluated in clinical trials; however, no registered antivirals have been approved for clinical therapy. In this study, we established a high-throughput screening (HTS) system based on CHIKV 26S mediated insect cell fusion inhibition assay. Our screening system was able to search potential anti-CHIKV dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 33 publications
1
84
1
10
Order By: Relevance
“…We also demonstrated that NTZ suppresses multiple post-entry stages of RV infection as it was observed for other viruses (La Frazia et al, 2013;Shi et al, 2014;Wang et al, 2016). It was more effective at the early stages of the replication cycle and completely blocked RV infection at 10 μg/ml, the peak concentration of the drug (C max ) in human plasma after receiving a single 500-mg oral dose of NTZ (Broekhuysen et al, 2000); Alinia ® package insert.…”
Section: Discussionsupporting
confidence: 60%
“…We also demonstrated that NTZ suppresses multiple post-entry stages of RV infection as it was observed for other viruses (La Frazia et al, 2013;Shi et al, 2014;Wang et al, 2016). It was more effective at the early stages of the replication cycle and completely blocked RV infection at 10 μg/ml, the peak concentration of the drug (C max ) in human plasma after receiving a single 500-mg oral dose of NTZ (Broekhuysen et al, 2000); Alinia ® package insert.…”
Section: Discussionsupporting
confidence: 60%
“…This broad activity has led to its evaluation as a therapeutic agent for a number of cancers, including breast, colon, ovarian, prostate, and others [13][14][15][16]. It has also shown potential to treat bacterial and viral infections such as Bacillus anthracis [17], Pseudomonas aeruginosa [18] and Staphylococcus aureus [19], as well as SARS-CoV [20], Influenza [21], Chikungunya [22] and Zika [23] viruses. In addition to the above, niclosamide has been investigated as a potential anti-mycobacterial drug.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 76 shown CHIKV 26S mediated insect cell fusion assays could be used to search for anti-CHIKV drugs. From this platform, it was suggested the anti-alphaviruses properties of niclosamide (104) and nitazoxanide (105) also can affect CHIKV entry and transmission, which verified their potential use in human cells proved by U2OS cells (Table 6).…”
Section: Niclosamide and Nitazoxanidementioning
confidence: 99%
“…From this platform, it was suggested the anti-alphaviruses properties of niclosamide (104) and nitazoxanide (105) also can affect CHIKV entry and transmission, which verified their potential use in human cells proved by U2OS cells (Table 6). 76 2.2. Niclosamide and nitazoxanide can be promising compounds for the further development of anti-CHIKV drugs.…”
Section: Niclosamide and Nitazoxanidementioning
confidence: 99%